The role of denosumab in the prevention of hypercalcaemia of malignancy in cancer patients with metastatic bone disease. Issue 11 (July 2015) - Diel, Ingo J.; Body, Jean-Jacques; Stopeck, Alison T.; Vadhan-Raj, Saroj; Spencer, Andrew; Steger, Günther; von Moos, Roger; Goldwasser, François; Feng, Amy; Braun, Ada
Abstract Background We compared the activity of denosumab with zoledronic acid for delaying or preventing hypercalcaemia of malignancy (HCM) in patients with advanced cancer and bone metastases or with multiple myeloma. Methods Patient-level data were combined from two identically designed, randomised, double-blind, active-controlled, phase III trials of advanced cancer patients with breast cancer and other solid tumours (excluding breast or prostate cancer) or multiple myeloma. End-points included time to first on-study HCM, time to first and subsequent on-study HCM, proportion of patients experiencing HCM and proportion of patients experiencing recurrent HCM. Results Denosumab significantly delayed the time to first on-study HCM, representing a 37% reduction in the hazard ratio (HR) compared with zoledronic acid (HR, 0.63; 95% confidence interval (CI): 0.41–0.98; P = 0.042) and reduced the risk of developing recurrent HCM (time to first and subsequent on-study HCM) by 52% (rate ratio, 0.48; 95% CI: 0.29–0.81; P = 0.006). The median time on study was 12.9 months. Fewer patients receiving denosumab compared with zoledronic acid experienced an HCM event (1.7% versus 2.7%; P = 0.028). Of the 84 patients experiencing an HCM event, 40% of those receiving zoledronic acid experienced >1 event of HCM compared with 31% of those receiving denosumab. Conclusion Denosumab treatment was more efficacious than treatment with zoledronic acid in delaying or preventing HCM in advanced cancer patients with breast cancer, other solid tumours or multiple myeloma.